Do Financial Statement Users Judge Relevance Based on Properties of Reliability? - Kadous, Kathryn; Koonce, Lisa; Thayer, Jane M. (The Accounting Review, 2012)
ABSTRACT Relevance and reliability (now referred to as “representational faithfulness”) are qualities of financial information that both the Financial Accounting Standards Board and the International Accounting Standards Board use in setting standards for financial reporting. Despite their importance, very little research has addressed how financial statement users apply these constructs. Via experiments set within the fair value context, we show that users do not view them as independent constructs. Instead, variations in properties that are associated with the reliability of a measurement influence users' assessments of the relevance of fair value. The relationship between assessed relevance and assessed reliability is unidirectional, in that factors underlying reliability influence judgments of relevance, but factors underlying relevance do not influence judgments of reliability. Our findings are important because inappropriate assessments of relevance can influence firm valuation. The results are particularly meaningful in the context of fair value because such measurements can vary widely in reliability. JEL Classifications: M41.